2018
DOI: 10.1016/j.biopha.2018.08.064
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-300/NAMPT regulates inflammatory responses through activation of AMPK/mTOR signaling pathway in neonatal sepsis

Abstract: Our study provides evidence indicating that overexpressedmiR-300 enhances autophagy by targeting NAMPT through activation of the AMPK/mTOR signaling pathway in septic mouse models, indicating it may serve as a potential therapeutic target for sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
6
26
0
Order By: Relevance
“…These findings are consistent with our recent study in which, miR-206 was introduced as a potential inhibitor of NAD biosynthesis in HBC cells via direct binding to NAMPT 3´-UTR (21). Consistently, NAMPT 3´-UTR has been reported in a number of studies, as the potential target for a wide variety of miRNAs in other malignancies and diseases including miR-182 in the ossification of ligamentum flavum (38), miR-300 in neonatal sepsis (39), miR-34a in obesity (40), miR-206 in pancreatic cancer (41), miR-26b in colorectal cancer (42), miR-410 in pulmonary arterial hypertension (PAH) (43) and miR-182 in HIV-1 contaminated cells (44).…”
Section: Mir-154 Regulated Nampt By Direct Binding To Its 3′-utrsupporting
confidence: 92%
“…These findings are consistent with our recent study in which, miR-206 was introduced as a potential inhibitor of NAD biosynthesis in HBC cells via direct binding to NAMPT 3´-UTR (21). Consistently, NAMPT 3´-UTR has been reported in a number of studies, as the potential target for a wide variety of miRNAs in other malignancies and diseases including miR-182 in the ossification of ligamentum flavum (38), miR-300 in neonatal sepsis (39), miR-34a in obesity (40), miR-206 in pancreatic cancer (41), miR-26b in colorectal cancer (42), miR-410 in pulmonary arterial hypertension (PAH) (43) and miR-182 in HIV-1 contaminated cells (44).…”
Section: Mir-154 Regulated Nampt By Direct Binding To Its 3′-utrsupporting
confidence: 92%
“…These findings are consistent with our recent study in which, miR-206 was introduced as a potential inhibitor of NAD biosynthesis in HBC cells via direct binding to NAMPT 3´-UTR (33). Consistently, NAMPT 3´-UTR has been reported in a number of studies, as the potential target for a wide variety of miRNAs in other malignancies and diseases including miR-182 in the ossification of ligamentum flavum (39), miR-300 in neonatal sepsis (40), miR-34a in obesity (41), miR-206 in pancreatic cancer (42), miR-26b in colorectal cancer (43), miR-410 in pulmonary arterial hypertension (PAH) (44) and miR-182 in HIV-1 contaminated cells (45).…”
Section: Luciferase Reporter Assay Verifying the Predicted Interactiosupporting
confidence: 92%
“…Nampt is involved in many important biological processes, including survival, apoptosis, metabolism and angiogenesis (16). As a cytokine, an elevated concentration of Nampt has been observed in several inflammatory and autoimmune disorders, such as sepsis, atherosclerosis, systemic lupus erythematosus and Crohn's disease (17)(18)(19)(20). Previous studies have demonstrated an elevated plasma Nampt concentration in Hashimoto's thyroiditis (HT) patients (14).…”
Section: Discussionmentioning
confidence: 99%